1999
DOI: 10.1006/jabr.1998.7607
|View full text |Cite
|
Sign up to set email alerts
|

Some model theory over hereditary noetherian domains

Abstract: Questions in the model theory of modules over hereditary noetherian domains are investigated with particular attention being paid to differential polynomial rings and to generalized Weyl algebras. We prove that there exists no isolated point in the Ziegler spectrum over a simple hereditary generalized Weyl algebra A of the sort considered by Bavula [Algebra iAnaliz 4(1) (1992), 75 97] over a field k with char(iv) = 0 (the first Weyl algebra Al(k) is one such) and the category of finite length modules over A do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Such a point, being finitely presented and the injective hull of a simple module, is also open (e.g. [PrPu,3.7]). Therefore both O and ZspΛ are clopen in ZspΛ.…”
Section: The Ziegler Spectrum Of Qf-rings and The Stable Module Categorymentioning
confidence: 99%
“…Such a point, being finitely presented and the injective hull of a simple module, is also open (e.g. [PrPu,3.7]). Therefore both O and ZspΛ are clopen in ZspΛ.…”
Section: The Ziegler Spectrum Of Qf-rings and The Stable Module Categorymentioning
confidence: 99%
“…In [17] we have shown that over a wide class of rings, so-called generalized Weyl algebras (GWA), the complete classification of indecomposable pure injective modules is hardly possible since it would include a similar classification over the free algebra k X Y -a problem which is usually considered as hopeless. For instance, this class of algebras includes the first Weyl algebra A 1 k and any primitive quotient of Usl 2 k over a field k of characteristic zero.…”
Section: Introductionmentioning
confidence: 99%
“…Klingler and Levy [72] showed that the category of torsion modules over this ring is "wild" and their techniques can be used to show that there is a continuous pure-injective R-module. If M is any indecomposable R-module of finite length then the pure-injective hull,M , of M is indecomposable and it follows from a result of Bavula [12] that no such point is isolated (see [120]). In [120] it is shown that the set of points of this form is dense in Zg R and hence that there are no isolated points in Zg R .…”
mentioning
confidence: 99%
“…If M is any indecomposable R-module of finite length then the pure-injective hull,M , of M is indecomposable and it follows from a result of Bavula [12] that no such point is isolated (see [120]). In [120] it is shown that the set of points of this form is dense in Zg R and hence that there are no isolated points in Zg R . These and related results are proved in [120] for a class of rings, certain generalised Weyl algebras in the sense of [11], which includes the first Weyl algebra.…”
mentioning
confidence: 99%
See 1 more Smart Citation